СТІЙКІСТЬ NERIUM OLEANDER L. ДО РІЗКОЇ ГІПО- ТА ГІПЕРТЕРМІЇ - Нужина, Наталія; Гайдаржи, Ольга (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
B a c k g r o u n d . Global climate changes have a negative impact on the life of native plants, reducing biodiversity. But on the other hand, the increase in average annual temperature causes the natural migration of species and can make it possible to grow plants from warmer climatic zones, which are not yet widely cultivated in Ukraine. One of these plants is the valuable medicinal and highly decorative plant Nerium oleander L. The purpose of this work was to investigate the resistance of N. oleander plants to sharp hyperthermia and hypothermia. The obtained data can be used for the potential possibility of expanding the area of oleander cultivation or prolonging the terms of these plants using as street plants. M e t h o d s . The plants of the control group were grown in controlled conditions at a temperature of +26˚С during the day and 20˚С at night. For heat resistance, the experimental group was heated for 3 hours at a temperature of +40˚С in a thermostat, and a group of plants studied for cold resistance was kept for 3 hours in a refrigerating chamber at a temperature of +4˚С. The content of malondialdehyde was measured as an indicator of stress, the activity of superoxide dismutase and peroxidase, as the efficiency of the antioxidant system. The influence of the temperature factor on the pigment system of oleanders was observed with a spectrophotometer. R e s u l t s . The study of the sharp effects of hypothermia (+4 °С) and hyperthermia (+40 °С) showed that N. oleander plants withstand minor cold stress very well and cannot withstand sudden warming very well. The amount of MDA increased by two times under a sharp warming of the plants. Under both stress exposures, SOD activity increased more than twice in oleanders. The total amount of flavonoids decreases in both hypothermia and hyperthermia. Studies of the photosynthetic system also showed the absence of a negative effect of a sharp cooling down to +4°C. However, destruction of chlorophylls and carotenoids was observed after short-term heating to +40°С C o n c l u s i o n s . Studies of oleanders have shown the absence of a negative effect of a sharp cooling down to +4 °С and a pronounced stress reaction in plants to a short-term warming up to +40 °С. It is possible that sudden warming accompanied by low air humidity is negative for these plants.

Вступ. Глобальні зміни клімату негативно впливають на життєдіяльність аборигенних рослин, зменшуючи видове біорізноманіття. Але з іншого боку, підвищення середньорічної температури спричиняє природну міграцію видів і може дати змогу вирощувати рослини із тепліших кліматичних зон, які ще не широко культивуються в Україні. Однією з таких рослин є цінна лікарська та високодекоративна рослина Nerium oleander L. Метою даної роботи було дослідити стійкість рослин виду N. оleander до різкої гіпертермії та гіпотермії. Отримані дані можуть бути використані для потенційної можливості розширення ареалу вирощування олеандрів або пролонгування термінів використання цих рослин як вуличних. Методи. Рослини контрольної групи вирощували за температури +26˚С вдень та 20˚С вночі. Для жаростійкості першу дослідну групу прогрівали протягом 3 год. за температури +40˚С у термостаті, а групу рослин, що досліджували на холодостійкість, тримали 3 години в холодильній камері за температури +4˚С. За допомогою спектрофотометра вимірювали вміст малонового діальдегіда, як показника стресу, активність супероксид дисмутази та пероксидази, як ефективність антиоксидантної системи, та дивились вплив температурного чинника на пігментну систему олеандрів. Результати. Дослідження різкого впливу гіпотермії (+4 °С) та гіпертермії (+40 °С) показало, що рослини N. оleander дуже добре витримують незначний холодовий стрес і погано витримують різке прогрівання. Кількість МДА зросла вдвічі після різкого прогрівання рослин. Після обох стресових впливів у олеандрів більше ніж вдвічі збільшилась активність СОД. Загальна кількість флавоноїдів зменшується як при гіпо-, так і при гіпертермії. Дослідження фотосинтезуючої системи також показали відсутність негативного впливу різкого похолодання до +4°С. Однак, спостерігалось руйнування хлорофілів та каротиноїдів після короткочасного прогрівання до +40°С Висновки.  Дослідження олеандрів показали відсутність негативного впливу різкого похолодання до +4 °С та виражену стресову реакцію у рослин на короткочасне прогрівання до +40°С. Можливо різке прогрівання саме у супроводі низької вологості повітря є негативним для даних рослин.
Keywords: oleander; antioxidant system; heat resistance; cold resistance; antioxidant system; heat resistance; cold resistance; олеандр; антиоксидантна система; жаростійкість; холодостійкість; антиоксидантна система; жаростійкість; холодостійкість